2013
DOI: 10.3168/jds.2012-5574
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fat mobilization during early lactation differently affects feed intake, body condition, and lipid and glucose metabolism in high-yielding dairy cows

Abstract: Fat mobilization to meet energy requirements during early lactation is inevitable because of insufficient feed intake, but differs greatly among high-yielding dairy cows. Therefore, we studied milk production, feed intake, and body condition as well as metabolic and endocrine changes in high-yielding dairy cows to identify variable strategies in metabolic and endocrine adaptation to overcome postpartum metabolic load attributable to milk production. Cows used in this study varied in fat mobilization around cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

32
169
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 52 publications
32
169
7
3
Order By: Relevance
“…First, a time period of deep negative energy balance, in which breeding of the animals is not reccomended was chosen for follicle aspiration (1 st follicle aspiration, 37 ± 1.9 days post-partum). Secondly, a time period in which most of the high-yielding cows are in balanced energy metabolism and beginning of breeding is suggested was selected (2nd follicle aspiration, 70 ± 2.2 days post-partum), and thirdly, a time period in which dairy cows return to a positive energy balance and breeding success is known to reach its maximum was investigated (3 rd follicle aspiration, 108 ± 1.8 days post-partum) (Inchaisri et al 2011a,b;Weber et al 2013). As expected, our results showed that a lack of ovarian function is a problem for fertility in dairy herds during the postpartum period within the time period of negative energy balance (Lopez-Gatius et al 2002;Wiltbank et al 2006;Walsh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a time period of deep negative energy balance, in which breeding of the animals is not reccomended was chosen for follicle aspiration (1 st follicle aspiration, 37 ± 1.9 days post-partum). Secondly, a time period in which most of the high-yielding cows are in balanced energy metabolism and beginning of breeding is suggested was selected (2nd follicle aspiration, 70 ± 2.2 days post-partum), and thirdly, a time period in which dairy cows return to a positive energy balance and breeding success is known to reach its maximum was investigated (3 rd follicle aspiration, 108 ± 1.8 days post-partum) (Inchaisri et al 2011a,b;Weber et al 2013). As expected, our results showed that a lack of ovarian function is a problem for fertility in dairy herds during the postpartum period within the time period of negative energy balance (Lopez-Gatius et al 2002;Wiltbank et al 2006;Walsh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For aspiration of the pre-ovulatory follicles three time points were chosen in order to allow investigation of different time periods post-partum, which are marked by different metabolic characteristics (Weber et al 2013). First, a time period of deep negative energy balance, in which breeding of the animals is not reccomended was chosen for follicle aspiration (1 st follicle aspiration, 37 ± 1.9 days post-partum).…”
Section: Discussionmentioning
confidence: 99%
“…'Backfat thickness' is correlated with total body fat (Schroder and Staufenbiel, 2006), and allowed to differentiate body reserve mobilization among cows that calve with different degree of body fatness (Hammon et al, 2009;Weber et al, 2013). However, it does not take into account internal adipose depots, which may have different dynamics of mobilization during early lactation (Weber et al, 2013). Cows in the current study were at mid (prepartum) to low (postpartum) BCS range, and calved with homogenous levels of fatness, as indicated by BCS.…”
mentioning
confidence: 98%
“…However, statistical differences of 'backfat thickness' are due to the greater skin thickness (D0) observed in MONT, which became evident after the depletion of subcutaneous adipose and connective tissues (D1 − D0) postpartum. 'Backfat thickness' is correlated with total body fat (Schroder and Staufenbiel, 2006), and allowed to differentiate body reserve mobilization among cows that calve with different degree of body fatness (Hammon et al, 2009;Weber et al, 2013). However, it does not take into account internal adipose depots, which may have different dynamics of mobilization during early lactation (Weber et al, 2013).…”
mentioning
confidence: 99%
“…In concert with these energy-saving mechanisms, NEFA plasma concentrations are increased indicating that nutrients are provided by lipolysis (Gross et al, 2011;Weber et al, 2013). In addition, a marked elevation (179%) of the growth hormone-releasing and orexigenic peptide hormone ghrelin (Wertz-Lutz et al, 2006;Bradford and Allen, 2008) has been observed in all cows.…”
Section: Discussionmentioning
confidence: 99%